If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-25=-5(x+5)
We move all terms to the left:
-25-(-5(x+5))=0
We calculate terms in parentheses: -(-5(x+5)), so:We get rid of parentheses
-5(x+5)
We multiply parentheses
-5x-25
Back to the equation:
-(-5x-25)
5x+25-25=0
We add all the numbers together, and all the variables
5x=0
x=0/5
x=0
| 24.5-x-2=3+4x+5 | | 3w^2=-w | | 6w+2w+4=12 | | –5+6.2x=6.2x–6 | | 1/3x-2=2/5 | | 4y^2+8=0 | | -21=1-10x | | 1/3y-2=2/5 | | 3n-29=0 | | 3u^2-3u=0 | | -5y-(8y)=12 | | 3x+5=(-2)-4x | | -3(-6v+6)-8v=2(v-1)-4 | | 6x+3=8-7 | | 3x+3(3x-3)=17 | | 2x+3(3x-3)=17 | | 200x-20=90 | | w-15=5.7 | | 2(2x-30)=-72 | | 5(v+2)=2v-17 | | 2x+9=8x-31 | | 8x-6=-6-3x-x | | -1=7x-4 | | x^2+15x+64=20 | | x-2/6=0.5 | | 3/4-13d/16=7/8 | | -51=-7x+5 | | -2(1-5x)=3x+26 | | 2x^2-6x-40=0 | | 7x+30=19x^2 | | 7z+3=-2z=-12 | | x+(-22)=35 |